1999
DOI: 10.1103/physrevlett.82.5353
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from Magnetism to Unconventional Superconductivity in a Series ofCexCu2Si2

Abstract: We report on the basis of Cu-NQR measurements that the ground state in a series of Ce x Cu 2 Si 2 compounds evolves from a magnetically ordered phase at x 0.975 to a heavy-electron superconducting (SC) phase at x 1.025. We have found that the sample of x 0.99 does not exhibit any trace of magnetic phase transition down to 0.012 K. Slow magnetic fluctuations with low frequencies comparable to the NQR frequency develop rapidly below T m ϳ 1.2 K. This unusual "critical magnetic phase" can coexist with the SC phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
95
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 22 publications
14
95
0
Order By: Relevance
“…Finally, we compare the present results with those on Ce 0.975 Cu 2 Si 2 (Ce0.975) where an AFM order was reported below T N ∼ 0.6 K [9,43]. Unlike the Ge substituted samples, however, any signature of superconductivity was not observed up to P = 2 GPa in Ce0.975, and the AFM order persists [44].…”
Section: The Af and Sc Phase Diagram In Cecu2si2mentioning
confidence: 69%
See 1 more Smart Citation
“…Finally, we compare the present results with those on Ce 0.975 Cu 2 Si 2 (Ce0.975) where an AFM order was reported below T N ∼ 0.6 K [9,43]. Unlike the Ge substituted samples, however, any signature of superconductivity was not observed up to P = 2 GPa in Ce0.975, and the AFM order persists [44].…”
Section: The Af and Sc Phase Diagram In Cecu2si2mentioning
confidence: 69%
“…From the Cu-NQR measurements [9], we showed that the A-phase at H = 0 behaves as a marginal AFM state, where slowly fluctuating AFM waves propagate over a long distance and coexist with the SC state. It is quite unusual that their characteristic frequencies range in NQR frequencies of 3 ∼ 4 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, if we assume µ ef f = 1µ B and R Tc = 1 in U-based systems, we obtain K i (α) ≈ 4 that is comparable to that in Ce-based HFS's in which antiferromagnetic spin fluctuations are dominant and systems are close to a magnetic quantum critical point. 62,63 This is, however, unlikely to occur in U-based HFS's becasue 1/T 1 T = const. behavior strongly suggests that antiferromagnetic spin fluctuations are not dominant at low T 's.…”
Section: Anisotropic Quasi-particle Korringa Relationmentioning
confidence: 99%
“…Despite intense research, the precise form of the superconducting order parameter remains elusive. Measurements of the relaxation rate of the nuclear quadrupolar resonance [7,8] and specific heat under pressure [9] have yielded evidence for an unconventional order parameter. Angle-resolved resistivity measurements of the upper critical field H c2 exhibit a fourfold symmetry of H c2 consistent with a d xy symmetry of the order parameter [10].…”
Section: Introductionmentioning
confidence: 99%